1999
DOI: 10.1093/nar/27.8.1859
|View full text |Cite
|
Sign up to set email alerts
|

A conserved motif in group IC3 introns is a new class of GNRA receptor

Abstract: Terminal tetraloops consisting of GNRA sequences are often found in biologically active large RNAs. The loops appear to contribute towards the organization of higher order RNA structures by forming specific tertiary interactions with their receptors. Group IC3 introns which possess a GAAA loop in the L2 region often have a phylogenetically conserved motif in their P8 domains. In this report, we show that this conserved motif stands as a new class of receptor that distinguishes the sequences of GNRA loops less … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 22 publications
1
38
0
Order By: Relevance
“…1 and S1B) (27). Stability of the P5/DP5 interface has been shown to depend on the concentration of Mg 2þ ions (28,31). In the wild-type interface, 5e10 mM Mg 2þ is sufficient to form the highly stable P5/DP5 interface.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 and S1B) (27). Stability of the P5/DP5 interface has been shown to depend on the concentration of Mg 2þ ions (28,31). In the wild-type interface, 5e10 mM Mg 2þ is sufficient to form the highly stable P5/DP5 interface.…”
Section: Resultsmentioning
confidence: 99%
“…Assembly of the P5/ DP5 interface is supported by three tertiary interactions (L5beP6, L5ceL2, and P5aeP4) (27). The P5aeP4 interaction is structurally invariable (18) and alternative L5beP6 interactions have been exploited (28). Therefore, we primarily focused on generating an alternative L5ceL2 interaction (also called P14 base pairs).…”
mentioning
confidence: 99%
“…Examples of such interactions with unknown structures include the IC3 motif from the group IC3 introns and recently identified loop-loop interaction in a hammerhead ribozyme. 42,43 Materials and Methods…”
Section: Structure Of the Gaaa Tetraloop-receptor Complexmentioning
confidence: 99%
“…7A). When the interaction between P1 and P3b was disrupted by replacing the P1 GAAA loop with a GUGA loop (Costa and Michel 1997;Ikawa et al 1999), the resulting variant (P1 GUGA) showed little activity (Fig. 7B).…”
Section: Structural Organization Of the Yfl Ribozymementioning
confidence: 99%